Neurocognitive Impairment After Propofol With Relevance for Neurosurgical Patients and Awake Craniotomies—A Prospective Observational Study - Zech, Nina; Seemann, Milena; Luerding, Ralf; Doenitz, Christian; Zeman, Florian; Cananoglu, Hamit; Kees, Martin G.; Hansen, Ernil (Frontiers in Pharmacology, 2021)
Background Short-acting anesthetics are used for rapid recovery, especially for neurological testing during awake craniotomy. Extent and duration of neurocognitive impairment are ambiguous. Methods Prospective evaluation of patients undergoing craniotomy for tumor resection during general anesthesia with propofol (N of craniotomies=35). Lexical word fluency, digit span and trail making were tested preoperatively and up to 24h after extubation. Results were stratified for age, tumor localization and hemisphere of surgery. Results in digit span test were compared to 21 patients during awake craniotomies. Results Word fluency was reduced to 30, 33, 47, and 87% of preoperative values 10, 30, 60 min and 24h after extubation, respectively. Digit span was decreased to 41, 47, 55, and 86%. Performances were still significantly impaired 24h after extubation, especially in elderly. Results of digit span test were not worse in patients with left hemisphere surgery. Significance of difference to baseline remained, when patients with left or frontal lesions, i.e. brain areas essential for these tests, were excluded from analysis. Time for trail making was increased by 87% at one hour after extubation, and recovered within 24h. In 21 patients undergoing awake craniotomies without pharmacological sedation, digit span was unaffected during intraoperative testing. Conclusion Selected aspects of higher cognitive functions are compromised for up to 24 hours after propofol anesthesia for craniotomy. Propofol and the direct effects of surgical resection on brain networks may be two major factors contributing (possibly jointly) to the observed deficits. Neurocognitive testing was unimpaired in patients undergoing awake craniotomies without sedation.